Neuroimaging of white matter abnormalities in pediatric hydrocephalus - Yuan, Weihong; McAllister, James P., II; Mangano, Francesco T. (Journal of Pediatric Neuroradiology, 2013)
Hydrocephalus (HCP) is a severe pathologic condition in which the ventricular system enlarges in response to abnormal cerebrospinal fluid production and absorption mechanisms. While accumulating evidence implicates damage to various white matter (WM) structures as one of the major neurobiological mechanisms underlying poor behavioral outcomes in children with HCP, current evaluation of such damage remains limited. Diffusion tensor imaging (DTI) is a unique magnetic resonance technique that exploits differences in the diffusion properties of water molecules in different tissue. Anisotropic diffusion properties, as measured by DTI, are strongly influenced by the micro-structural components of WM and thus can help to assess the properties in tissue constituents, tissue microstructure and cytoarchitecture. Initial clinical studies have shown that DTI is a sensitive imaging tool for investigating WM damage as well as the extent of recovery in HCP. A key study has shown that the periventricular WM and corona radiata in children between 12–18 years exhibited increased pre-operative fractional anisotropy (FA) driven by a slightly increased axial diffusivity and a more dramatic decreased radial diffusivity. Post-operatively the FA in these regions returned to normal in most patients. In contrast, the corpus callosum was found to have low FA pre-operatively which did not respond to cerebrospinal fluid diversion surgery. A more recent study reported a similar lower FA and higher mean diffusivity in the corpus callosum in infants. However, the abnormalities in the internal capsule were found to be more heterogeneous. Longitudinal study showed that most DTI measurements returned to normal post-operatively. In experimental studies, similar abnormalities in DTI were found in both neonatal and infantile rats with induced HCP. These findings correlated with increased astrocyte and microglial reactivity and reduced myelination. This review also discusses interpretations regarding the different patterns of DTI abnormalities seen in HCP in different WM regions. Overall, support is growing for DTI as a useful non-invasive imaging tool in the diagnosis and treatment of pediatric hydrocephalus.
Keywords: Hydrocephalus; diffusion tensor imaging; corpus callosum; internal capsule; cerebral spinal fluid